2019
DOI: 10.1371/journal.pone.0224969
|View full text |Cite
|
Sign up to set email alerts
|

A fecal sequel: Testing the limits of a genetic assay for bat species identification

Abstract: DNA metabarcoding assays are powerful tools for delving into the DNA in wildlife feces, giving unprecedented ability to detect species, understand natural history, and identify pathogens for a range of applications in management, conservation, and research. Next-generation sequencing technology is developing rapidly, which makes it especially important that predictability and reproducibility of DNA metabarcoding assays are explored together with the post-depositional ecology of the target taxon’s fecal DNA. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 47 publications
1
28
1
Order By: Relevance
“…Both vampire species that we detected fed on blood from domestic birds and cattle [ 53 , 54 ]. Although we did not detect cattle in our samples, Walker et al [ 35 ] genetically identified cattle from D . rotundus feces, so it is not unrealistic to conclude that domestic birds could be either prey of V .…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Both vampire species that we detected fed on blood from domestic birds and cattle [ 53 , 54 ]. Although we did not detect cattle in our samples, Walker et al [ 35 ] genetically identified cattle from D . rotundus feces, so it is not unrealistic to conclude that domestic birds could be either prey of V .…”
Section: Discussioncontrasting
confidence: 65%
“…spectrum [ 2 , 7 , 13 , 17 – 19 ]. The SFF marker, which is optimized for identifying bat species from fecal samples [ 35 , 36 ], followed by the 12S marker [ 33 ], provided the greatest diversity of identifiable vertebrate taxa with 10 species confirmed by both markers. The ANML primer [ 32 ] detected fewer vertebrate taxa; however, it was the only one that detected Megascops cooperi .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, in all fecal DNA metabarcoding studies, the gold standard is to collect fresh feces for maximum DNA recovery. Research carried out by Walker et al (2019) revealed that DNA in bat guano, which can be used for host identification, can be recovered up to at least 2.5 years in dry and cool roosts, but at 100% relative humidity, feces that are younger than 6 months are needed. Moisture, particularly in combination with high temperature, promotes the growth of microbes, and thus further DNA There are two versions of abstract in the manuscript.…”
Section: Replies To Reviewers' Commentsmentioning
confidence: 99%
“…Identification of bats from guano-derived DNA dates back to the early 2000 (Zinck et al, 2004). This approach has been successfully applied to fresh and modern -up to 20 years -samples (e.g., Brown et al, 2017;Walker et al, 2019;Guan et al, 2020). Overall, in all fecal DNA metabarcoding studies, the gold standard is to collect fresh feces for maximum DNA recovery.…”
Section: Identification Of the Bat Dnamentioning
confidence: 99%